(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Blue Economy is a recently coined concept in resource planning. The concept encompasses all economic activities that depend on the sea, such as tourism, maritime transport, energy and fishing. Blue economy facilitates the sustainable growth of a nation’s economy; as the oceans and seas are engines of the global economy with great potential for livelihoods enhancement, and a catalyst for economic growth and development. The study unravels appropriate mechanism for poverty alleviation in Nigeria by unlocking the opportunities offered by the blue economy. The study conceptually reviewed existing literature as a basis for obtaining an in-depth understanding of how blue economy potentials can provide alternative livelihoods asides generating employment opportunities in fisheries, tourism, and other ocean based industries that could boost the wellbeing of households and their income generating capability in Nigeria. It is revealed that blue economy has far-reaching potential for expanding economic activities and poverty reduction if the economic, social, technological, cultural and environmental challenges fettering the development of the sector are properly addressed. Consequently, the study recommends strong political will and robust institutions for effective development and implementation of blue economy policies in order to bolster livelihood activities in Nigeria. The need to establish thorough policy coordination and stakeholder engagement to provide formidable structure for the development of blue economy in Nigeria is suggested.